Software de auxílio pedagógico para ensino de consultas simples a banco de dados - Delfino, Wirlley de Oliveira (2021)
With the advancement of technologies, it is now possible to develop tools that help in various processes, such as the teaching process, creating tools that help learning. Thus, this work deals with the elaboration of a software to aid in the learning of database queries, being a software capable of executing an SQL query and then showing the processes that are carried out to obtain the final result. For the implementation, the Visual Studio Code development environment and the PostGreSQL database were used. For project management, the Feature Driven Development methodology was used.